Fatal Necessity : British Intervention in New Zealand, 1830-1847. - Adams, Peter (Bridget Williams Books, 2013)
Fatal Necessity, now re-issued as an e-book, is a detailed examination of the circumstances leading to British intervention and hence to the Treaty of Waitangi.